Tormentic acid confers protection against oxidative stress injury in rats with Parkinson's disease by targeting the Wnt/Î²-catenin signaling pathway - Yue, Yamin; Qiao, Bai; Jiang, Xiaohua (Cellular and Molecular Biology, 2020)
Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease (AD). Studies have shown that oxidative stress (OS) may contribute to the cascade of reactions leading to the degeneration of dopaminergic neurons in the brain. The present study investigated the protective effect of tormentic acid (TMA) on OS-induced injury in rat model of PD, and the underlying mechanism. Evaluation of learning and memorizing ability was done using Morris water maze (MWM) test. The activities of superoxide dismutase (SOD) and glutathione peroxidase (GPx), and level of malondialdehyde (MDA) in substantia nigra were determined using enzyme-linked immunosorbent assay (ELISA). The protein and mRNA expressions of Î²-catenin, GSK-3Î², and GSK-3Î²-Ser9 were determined using real-time quantitative polymerase chain reaction (qRT-PCR) and Western blotting. The effect of TA on cell viability and proliferation was determined in vitro on rat adrenal pheochromocytoma (PC12) cell line using MTT assay. The results showed that the escape latency of rats in negative control group was significantly higher than that in normal control group (p < 0.05). However, treatment with TMA significantly and time-dependently reduced the escape latency of the rats (p < 0.05). The extent of apoptosis was significantly reduced after treatment with TMA (p < 0.05). Besides, treatment with TMA significantly increased the viability of brain cells (p < 0.05). The activities of SOD and GPx were significantly lower in negative control group than in normal control group, but were significantly increased after treatment with TMA (p < 0.05). The level of MDA was significantly higher in negative control group than in normal control group, but was significantly reduced after treatment with TMA (p < 0.05). The results of qRT-PCR and Western blotting showed that treatment with TMA significantly activated Wnt/Î²-catenin signaling pathway (p < 0.05). TMA treatment significantly reversed the effect of 6-hydroxydopamine on the expression levels of these proteins and their mRNAs (p < 0.05). These results suggest that TMA confers protection against OS-induced injury in rats with PD by targeting the Wnt/Î²-catenin signaling pathway.